Ambroxol Therapy as an Antibiofilm Candidate in Diabetic Ulcer Patients - Wahyuddin, Munifah; Sari, Ika Puspita; Asdie, Rizka Humardewayanti; Nuryastuti, Titik (Program Studi Farmasi Universitas Mandala Waluya, 2025)
Patients with diabetic ulcers are susceptible to infection because the tissue in their extremities is constantly exposed to various pathogenic bacteria, so biofilm formation plays an important role in developing the disease. Based on previous studies, ambroxol can inhibit the formation of biofilm bacteria. The purpose of this study was to identify biofilm-forming bacteria, prove that ambroxol has the potential to inhibit and eradicate biofilms formed by bacteria in diabetic ulcers and analyse the potential of ambroxol in eradicating biofilms formed by bacteria in diabetic ulcer patients based on PEDIS and SEM scores. The method used was a 96-well microtiter plate assay (MtPA) with crystal violet and MTT staining techniques, a test using human samples with a quasi-experimental method with sampling carried out by nonprobability sampling. The samples used were diabetic ulcer patients with culture results forming biofilms. The results obtained identified 3 clinical isolates that formed biofilms with 100% Gram-negative bacteria, including two isolates of Pseudomonas aeruginosa and one isolate of Escherichia coli with the ability to form biofilms are moderate. Ambroxol effectively inhibits and eradicates 50% of biofilms formed by diabetic ulcer bacteria at a minimum concentration of 1 mg/ml. Based on the PEDIS score and SEM images of diabetic ulcer patients, there was a decrease in the PEDIS score in each patient, with an average score of 2. Several studies have demonstrated that combining Ambroxol with antimicrobials can synergistically enhance the antibiotic's efficacy against biofilms. The co-administration of Ambroxol with other antimicrobial agents represents a promising approach to improving antibiotic effectiveness. Nevertheless, careful consideration must be given to the concentration of Ambroxol used.